2021
DOI: 10.3390/agronomy11030596
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Polyploidization of Thymus vulgaris L. and Its Effect on Composition of Essential Oils

Abstract: The aim of this work was to find an effective protocol for in vitro propagation and to perform the in vitro polyploidization of diploid Thymus vulgaris (2n = 30) using two experimental methods based on the use of oryzalin, an antimitotic agent. The ploidy level of the obtained shoots was checked by flow cytometric analysis. The most efficient conditions for inducing polyploidy were oryzalin concentrations of 0.346 and 1.73 mg L−1 present in the medium for two weeks. The vital polyploid shoots were multiplied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
2
24
1
Order By: Relevance
“…As reported by Trojak-Goluch and Skomra [73] as well as Švécarová et al [78], hop tetraploids showed poorer acclimatisation to field conditions and poorer rooting. Similar traits were displayed by tetraploids of T. vulgaris [79] and C. sativa [74]. Contrasting results were obtained by Tang et al for tetraploids of P. tomentosa, whose seedlings were characterised by a strong root system and high acclimatisation ability (90%) [82].…”
Section: Species Morphological Traits Ploidy Referencesmentioning
confidence: 67%
See 4 more Smart Citations
“…As reported by Trojak-Goluch and Skomra [73] as well as Švécarová et al [78], hop tetraploids showed poorer acclimatisation to field conditions and poorer rooting. Similar traits were displayed by tetraploids of T. vulgaris [79] and C. sativa [74]. Contrasting results were obtained by Tang et al for tetraploids of P. tomentosa, whose seedlings were characterised by a strong root system and high acclimatisation ability (90%) [82].…”
Section: Species Morphological Traits Ploidy Referencesmentioning
confidence: 67%
“…It involves a 2-week culture of nodal fragments on MS medium with the addition of oryzalin. The number of polyploids obtained this way represented 10.3 to 66.7% of the regenerants [79]. The study by Švécarová et al showed that for H. lupulus, it is possible to obtain a greater number of polyploids (70% of all tested) using this method [78].…”
Section: Type Of Plant Tissuementioning
confidence: 94%
See 3 more Smart Citations